Optimization of turbidity removal process of ultra-low alcohol strong-flavor Baijiu by active carbon with response surface method - WEN Xingke, ZHANG Suyi, NI Bin, SHAO Yan, AO Zonghua, JIA Junjie, WANG Yu, CHEN Zhilin, JIANG Wenyi (Zhongguo niangzao)
In order to broaden the market of Baijiu, meet the needs of young consumers, and solve the problems of traditional low alcohol Baijiu such as thin liquor body and turbidity, light loss and precipitation in the process of alcohol reduction, the ultra-low alcohol strong-flavor (Nongxiangxing) Baijiu was produced by turbidity removal treatment with alcohol activated carbon adsorption and filtration. On the basis of single factor tests, a 4 factors 3 levels response surface tests were conducted using Box-Behnken central composite design. Using the activated carbon addition, activated carbon pores mesh number, standing adsorption time and temperature as the influencing factors, the effects of various factors on the transmittance and sensory score of ultra-low alcohol strong-flavor Baijiu were explored, and the turbidity removal process of ultra-low alcohol strong-flavor Baijiu was optimized. The results showed that when the alcohol reduction of strong-flavor Baijiu was less than 25%vol, the optimal turbidity removal process conditions for ultra-low alcohol strong-flavor Baijiu by activated carbon were as follows: activated carbon pores mesh number 400 mesh, activated carbon addition 0.54‰, static adsorption temperature 5 ℃, and time 20.3 h. Under these optimal conditions, the transmittance and sensory score of ultra-low alcohol strong-flavor Baijiu were 92% and 87 points, respectively.